2008
DOI: 10.1117/12.778786
|View full text |Cite
|
Sign up to set email alerts
|

Near-IR imaging of erbium laser ablation with a water spray

Abstract: Near-IR (NIR) imaging can be used to view the formation of ablation craters during laser ablation since the enamel of the tooth is almost completely transparent near 1310-nm 1 . Laser ablation craters can be monitored under varying irradiation conditions to assess peripheral thermal and transient-stress induced damage, measure the rate and efficiency of ablation and provide insight into the ablation mechanism. There are fundamental differences in the mechanism of enamel ablation using erbium lasers versus carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…In the present study, constant water spray was used during the whole laser irradiation process for both Er:YAG and Er,Cr:YSGG lasers, as it is also used in clinical treatments of enamel and dentin, either for cavity preparation or for other surface modifications. The importance of continuous spray application is also confirmed by Darling et al who observed “very clean without large cracks” ablation craters and no accompanying thermal side effects [ 19 ]. The water spray acts as a mediator for efficient ablation and minimizes the risk of adverse thermal effects in the pulp tissue.…”
Section: Discussionmentioning
confidence: 78%
“…In the present study, constant water spray was used during the whole laser irradiation process for both Er:YAG and Er,Cr:YSGG lasers, as it is also used in clinical treatments of enamel and dentin, either for cavity preparation or for other surface modifications. The importance of continuous spray application is also confirmed by Darling et al who observed “very clean without large cracks” ablation craters and no accompanying thermal side effects [ 19 ]. The water spray acts as a mediator for efficient ablation and minimizes the risk of adverse thermal effects in the pulp tissue.…”
Section: Discussionmentioning
confidence: 78%
“…The currently accepted theory for the mechanism of erbium laser ablation of dental hard tissues (enamel, dentine, cementum and bone) is a photo-mechanical action based on micro-explosions of water within the target. Conversion of the water to steam generates an increase in pressure, leading to micro-explosions [104,105]. These same mechanisms also apply to the ablation of dental plaque biofilms and dental calculus.…”
Section: Factors Influencing Ablationmentioning
confidence: 96%
“…Over the past two years we have presented work showing that near-IR (NIR) imaging can be used to image the formation of craters during IR laser ablation since the enamel of the tooth is almost completely transparent near 1310-nm (1)(2)(3). These studies showed that there is great potential for NIR imaging to monitor laser-ablation events in real-time to assess safe laser operating parameters by imaging thermal and stress-induced damage, elaborate the mechanisms involved in ablation such as dehydration, monitor removal of demineralized enamel and investigate the dynamic changes in the transparency of enamel with water loss.…”
Section: Introductionmentioning
confidence: 99%